Nina's Love Betrayal in The Drama Script The Seagull by Anton Chekov - Della Eka Putri; Sri Kusumo Habsari; Susanto Susanto (Universitas Sebelas Maret, 2022)
Drama is a form of literary work that describes the reality of human life which is presented in the form of movement. In this case, one of the famous dramas